Hubungan Perilaku Keluarga Sadar Gizi (KADARZI) dengan Kejadian Stunting di Desa Ngabul Kecamatan Tahunan Kabupaten Jepara - Zulfa, Siti Ani; Ana Zumrotun Nisak; Dwi Astuti (Journal of Midwifery and Health Science of Sultan Agung, 2025)
One of the nutritional problems that occurs in children is short toddlers, that is, their height does not match their age or what is usually called stunting. Based on the health profile of Jepara district, the annual stunting incidence rate in community health centers is ranked 11th out of 22 community health centers in Jepara district, reaching 10.68% of stunted toddlers in 2022. With this phenomenon, researchers are interested in conducting research with the title the relationship between Kadzi behavior and the incidence of stunting. Objective: to find out how the level of behavior of the community, especially mothers who have toddlers aged 24-60 months, to find out what the nutritional status of toddlers is based on TB/U, and whether there is a relationship between level behavior and the nutritional status of children. Research method: The type of research used is quantitative research with correlation analytical methods. Data collection was carried out cross-sectionally by conducting interviews with 41 respondents and reading a checklist containing 5 indicators. Respondents only gave a tick (√) to the selected answer. The statistical data test in this research was using chi square test analysis. Results: the majority of mothers did not behave Kadarzi, the condition of the toddlers was not stunted, and there was no relationship between Kadarzi behavior and the incidence of stunting.Conclusion: Kadarzi behavior does not affect the condition of stunted toddlers.